PENERAPAN ALGORITMA HILL CIPHER DAN PERMUTASI PADA SISTEM KRIPTOGRAFI POLYALPHABETIC - Lukmaini, Sindi; Wira Tama, Yanuar Bhakti; Nugraheni, Kartika (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN (EPSILON: JOURNAL OF PURE AND APPLIED MATHEMATICS), 2024)
TTechnological advances have a great influence on facilitating long-distance communication, one of which is exchanging messages. The security of a message is an important aspect of protecting sensitive information. Cryptography is a branch of science that aims to maintain the confidentiality, integrity, and authenticity of messages in communication. One of the cryptographic methods used is Hill Cipher, which converts plaintext into ciphertext using a key matrix, but Hill Cipher is vulnerable to cryptanalysis attacks, especially if the key matrix is not chosen properly. Based on these problems, this research was conducted by applying the Hill Cipher algorithm with permutation as an additional layer of security. This study aims to analyze the effect of the message and key matrix on the performance of computation time in the encryption and decryption process of Hill Cipher combined with permutation, where the message characters are limited to 26 alphabetic characters and the use of Hill block length and permutation techniques is set at 5 characters. The simulation results show the average performance of computation time on the encryption and decryption process is 0.000083199 seconds and 0.000113493 seconds for a message with 707 characters. The key matrix used must be invertible, and the performance of computation time on encryption and decryption with different keys is 0.000094817 seconds and 0.00025938 seconds.